2015
DOI: 10.1063/1.4905278
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic spin dephasing of impurity-bound electron spins in ZnO

Abstract: We investigate the electron spin dynamics of n-type c-axis oriented bulk zinc oxide (ZnO) by using time-resolved Kerr rotation and resonant spin amplification measurements. Calculating resonant spin amplification using an anisotropic spin dephasing model reveals that there are two species involved in the spin dynamics, which we attribute to conduction and impurity-bound electron spins, respectively. We find that the impurity-bound electron spin dephasing mechanism is strongly anisotropic due to anisotropic exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Furthermore, in n-type bulk ZnO, it has been reported that for donor-bound electrons the spin relaxation is strongly anisotropic. 7 It was claimed that the defects present in the sample due to impurities, induce bound exciton in the vicinity of donor states which further contribute to the spin signal. This contribution to the bound electron spins at donor sites is more predominant at low temperatures and leads to relaxation anisotropy.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, in n-type bulk ZnO, it has been reported that for donor-bound electrons the spin relaxation is strongly anisotropic. 7 It was claimed that the defects present in the sample due to impurities, induce bound exciton in the vicinity of donor states which further contribute to the spin signal. This contribution to the bound electron spins at donor sites is more predominant at low temperatures and leads to relaxation anisotropy.…”
Section: Resultsmentioning
confidence: 99%
“…Detailed study of spin relaxation anisotropy as a function of experimental parameters (namely, sample temperature, pump-probe delay and optical power) can be found in Ref. [24].The observed long T * 2 in the out-of-plane direction for both sample A and B stipulates that the scattering-induced DP mechanism is weak in the studied structures [12]. However, combined with the inhomogeneous spread of g-factor it leads to a strong T * 2 reduction.…”
Section: Spin Dynamics In Sample Bmentioning
confidence: 99%
“…In bulk semiconductors with wurtzite or zinc-blende crystalline structures, the antisymmetric part of the anisotropic exchange of the localized electrons is dominated by Dzyaloshinskii-Moriya 15 interaction (DMI) 63,64 which is the first-order perturbation in SOI of Rashba 65 showing anisotropic dephasing in bulk GaN and impurity-bound electrons in n-doped ZnO. 54,55 There have been theoretical and experimental demonstrations of magnetic orderings in semiconductors. 52,56,60,[67][68][69][70][71][72][73][74][75][76][77][78][79][80][81][82][83] In order to be more specific, we propose a system of interstitial impurities and oxygen vacancies in a metal-oxide.…”
Section: B Physical Feasibility Of the S M -Mechanismmentioning
confidence: 99%